Management of Islamic Religious Education Learning in Developing Students’ Moderate Character - Fitriani Fitriani; Yufi Mohammad Nasrullah; Fiqra Muhamad Nazib (Nidhomiyyah: Jurnal Manajemen Pendidikan Islam, 2026)
The decline of moral values among students represents a serious challenge in Indonesian education, requiring systematic and well-managed learning approaches as a strategic response. This study aims to examine and analyze the management of Islamic Religious Education (PAI) learning in shaping students’ moderate character at SMA Negeri 1 Garut. Employing a descriptive qualitative approach with a case study design, data were collected through semi-structured interviews, observations, and documentation involving teachers and students. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings reveal that PAI learning management is implemented systematically based on four core management functions: planning, organizing, implementing, and supervising. Learning planning is carried out through the formulation of learning objectives, learning contracts, and instructional modules aligned with learning outcomes. Learning organization supports an inclusive, active, and meaningful learning environment through the management of learning activities, facilities, and the school environment as learning resources. The implementation of learning emphasizes a Student-Centered Learning approach through positive habituation practices, short sermons (kultum), student presentations, and demonstration-based instruction that actively engage students. Learning supervision is conducted through formative and summative assessments that evaluate cognitive, affective, and psychomotor domains. Overall, effective PAI learning management contributes to the internalization of moderate character values, including tolerance, anti-violence attitudes, national commitment, and cultural accommodation, which are reflected in students’ attitudes and daily behavior within the school environment.